2010
DOI: 10.1097/cji.0b013e3181b8bdb9
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Mood Changes and Psychiatric Symptoms During 12-month Low-dose Interferon-α Treatment in Patients With Malignant Melanoma

Abstract: The purpose of the present study was to evaluate the incidence, spectrum and extent of psychiatric symptoms in patients with malignant melanoma (MM) before and during adjuvant treatment with interferon-alpha (IFN-alpha). 850 patients with cutaneous MM of > or =1.5 mm tumor thickness received standard low-dose IFN-alpha 2a in this prospective multicenter trial of the Dermatologic Cooperative Oncology Group (DeCOG). Psychiatric symptoms were evaluated at baseline and after 3, 6, and 12 months with the Beck Depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 60 publications
3
31
1
Order By: Relevance
“…Our results are in line with the findings of Heinze et al [26] who reported a delayed increase of depression scores during low-dose interferon alpha treatment. They also found that only a low number of participants (5%) reached the level for clinically relevant depressive syndrome during the treatment, similar to our study.…”
Section: Depression In Melanoma Patientssupporting
confidence: 96%
“…Our results are in line with the findings of Heinze et al [26] who reported a delayed increase of depression scores during low-dose interferon alpha treatment. They also found that only a low number of participants (5%) reached the level for clinically relevant depressive syndrome during the treatment, similar to our study.…”
Section: Depression In Melanoma Patientssupporting
confidence: 96%
“…Our observation that patients with mental health services use before hd-ifn start were more likely to discontinue hd-ifn early is in keeping with findings from other ifn studies 18,19 . Capuron and Ravaud 19 observed a clear correlation between depression scores on treatment day 1 and at 4 weeks.…”
Section: Discussionsupporting
confidence: 80%
“…Capuron and Ravaud 19 observed a clear correlation between depression scores on treatment day 1 and at 4 weeks. In the Dermatologic Cooperative Oncology Group randomized trial of low-dose ifn for melanoma 18 , patients who had higher Beck Depression Inventory scores (≥5) before receiving ifn experienced increased odds, by a factor of 3, of early ifn discontinuation because of somatic or psychiatric effects (odds ratio: 3.09; 95% cl: 1.32, 7.27).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the cytokines IFNα and IL2, used effectively as therapy for hepatitis C and cancer, Arşiv Kaynak Tarama Dergisi . Archives Medical Review Journal increase the risk for the development of depression 28,29 . Alterations in cytokine production have also been observed in animal models.…”
Section: Cytokine Hypothesis and Depressionmentioning
confidence: 99%